2015
DOI: 10.1097/prs.0000000000001494
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Contralateral C7 Transfer for the Treatment of Traumatic Brachial Plexus Injury

Abstract: Background Contralateral C7 (CC7) transfer has been used for treating traumatic brachial plexus injury. However, the effectiveness of CC7 transfer remains a subject of debate. We performed a systematic review to study the overall outcomes of CC7 transfer to different recipient nerves in traumatic brachial plexus injuries. Methods A literature search was conducted using PubMed and EMBASE databases to identify original articles related to CC7 transfer for traumatic brachial plexus injury. The data extracted we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…During a contralateral C7 nerve root transfer operation, the injured nerve on the injured side is repaired by transferring the partial or total seventh cervical nerve on the uninjured side using a nerve graft with more myelinated nerve fibers than in other available donor nerves, providing sufficient power for neurotization [ 7 ]. According to Yang et al, functional free-muscle repair and nerve transfer have been commonly treated with contralateral C7 nerve root transfer, especially in some Asian countries [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…During a contralateral C7 nerve root transfer operation, the injured nerve on the injured side is repaired by transferring the partial or total seventh cervical nerve on the uninjured side using a nerve graft with more myelinated nerve fibers than in other available donor nerves, providing sufficient power for neurotization [ 7 ]. According to Yang et al, functional free-muscle repair and nerve transfer have been commonly treated with contralateral C7 nerve root transfer, especially in some Asian countries [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, when a normal cC7 root is transferred to the median nerve of the affected limb to restore wrist flexion, finger flexion, and hand sensation, a nerve graft of over 30 cm is needed to bridge the gap in adults [11]. Various reports showed that flexion restoration after transfer of the cC7 root to the median nerve was far from what could be expected [2, 1113]. Why might this be?…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that two major factors leading to poor restoration of hand function using the traditional C7 transfer method are the long distance between the cC7 root and the target muscle and an insufficient number of donor myelinated fibers to match the recipient nerves [2]. Hence, in attempts to achieve better recovery, the cC7 transfer has been modified to shorten the gap that needs to be bridged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the feeble and inconsistent return of extrinsic flexion seen over the years has led to diminishing interest in the cC7 transfer. [ 1 2 3 4 5 6 7 ] The direct repair of cC7 with lower trunk produced superior and consistent result in restoration of extrinsic finger flexion. [ 8 9 ] However, despite the landmark report from Beijing in 2013, very few other units have adopted this technique.…”
Section: Introductionmentioning
confidence: 99%